2010
DOI: 10.1007/s11692-010-9080-9
|View full text |Cite
|
Sign up to set email alerts
|

Age, Body Size, and Sexual Dimorphism in Size and Shape in Salamandrella keyserlingii (Caudata: Hynobiidae)

Abstract: In organisms with determinate growth, sexual size dimorphism (SSD) occurs before maturity during the developmental process of growing apart, an ontogenetic perspective on the evolution of SSD. If the direction of SSD (female-larger SSD) is known, patterns of growth can be tested with one-tailed statistical distributions. In indeterminate growing organisms as well, does SSD occur before maturity? If it occurs, whether is females' larger mean body size caused by a difference in age at maturity, age-specific size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
1
34
0
5
Order By: Relevance
“…For B. andrewsi, adult females significantly exceeded adult males in body size, a condition seen in about 90% of anuran species (Shine, 1979). Several proximate causes have been invoked, including sex differences in growth rate, age structure, age at maturity, and adult survivorship in explaining sexual size dimorphism (Halliday and Tejedo, 1995;Monnet and Cherry, 2002;Hasumi, 2010). Previous studies on this species showed that males have smaller age at maturity, average age and growth rate than females (Liao, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For B. andrewsi, adult females significantly exceeded adult males in body size, a condition seen in about 90% of anuran species (Shine, 1979). Several proximate causes have been invoked, including sex differences in growth rate, age structure, age at maturity, and adult survivorship in explaining sexual size dimorphism (Halliday and Tejedo, 1995;Monnet and Cherry, 2002;Hasumi, 2010). Previous studies on this species showed that males have smaller age at maturity, average age and growth rate than females (Liao, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The sexual dimorphism of salamanders has attracted considerable interest in evolutionary biology (e.g., Halliday & Arano 1991;Kalezić et al 1992;Andersson 1994;Malmgren & Thollesson 1999;Serra-Cobo et al 2000;Ivanović et al 2008), but few studies have focused on Asian salamanders (Kuzmin 1995;Hasumi 2001Hasumi , 2010Poyarkov et al 2012). …”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…). Secondly, SSD can start to occur after hatch but before fledging, as a result of differences in the duration or rate of growth (Leigh & Shea , Hasumi , Zhang & Liu , Lok et al . ).…”
mentioning
confidence: 99%